Regulation of the growth and differentiation of Trypanosoma (Trypanozoon) brucei brucei in resistant (C57B1/6) and susceptible (C3H/He) mice - Black, Samuel J.; Sendashoga, Cyrie N.; Lalor, P.A.; Whitelaw, D.D.; Jack, R.M.; Morrison, W. Ivan; Murray, M. (Wiley, 1983)
Summary While Trypanosoma brucei brucei GUTat 3 were equally infective for C3H/Heand for C57B1/6 mice at doses ranging from 5 to 5 × 103 organisms and had similar prepatent periods in both strains of mice, infected C57B1/6 mice displayed lower parasitaemia, shorter times to parasite wave remission and survived for a longer time than infected C3H/He mice. Parasite growth and differentiation rates and host immune responses were similar for the first 5 days in both strains of mice after infection with 103 T.b.brucei GUTat 3 but, thereafter, parasite differentiation proceeded more rapidly and specific antibodies reached higher titres in C57B1/6 than in C3H/He mice. In contrast, parasite growth and differentiation rates were similar in irradiated mice of both strains. Furthermore, following inoculation of intact mice with irradiated T.b.brucei GUTat 3, C3H/Hemice actually mounted higher titred antibody responses than C57B1/6 mice showing that they were not intrinsically defective in their capacity to respond to GUTat 3 antigens. Parasite differentiation occurred at the same rate in irradiated (650r) C57B1/6 mice and in irradiated C57B1/6 mice reconstituted with syngeneic spleen cells although T.b.brucei GUTat 3 specific antibody was detected in the latter mice prior to peak parasitaemia. Furthermore, it was shown directly in C57B1/6 mice that there was no selective destruction of slender form T.b.brucei GUTat 3 parasites during the phase of accumulation of stumpy form parasites. These studies indicate that the more rapid differentiation of T.b.brucei GUTat 3 parasites in infected C57B1/6 mice as compared to infected C3H/Hemice was unlikely to be directly related to the more efficient antibody response in the infected C57B1/6 mice. The observations suggest that there might be an association between host mechanisms which regulate differentiation of T.b.brucei parasites and those which regulate antibody responses.